Effects of Kaolin Powder and Borax Addition on Adhesion Properties of Soy Protein Isolate-Based Adhesives - Budhijanto, Budhijanto; Widodo, Theresia Winona Rosari; Ramadhani, Gilang Afif Setya (Eksergi, 2024)
A low-cost strategy was developed to improve the adhesion properties and long shelf life of soy protein isolate-based adhesive, by using kaolin powder as filler and borax as an antifungal. Soy protein bioadhesive will be synthesized through denaturation using Sodium Lauryl Sulfate, followed by crosslinking using epoxy resin as a crosslinker, kaolin powder addition as filler, and borax addition to inhibit the fungal growth. Some analysis such as viscosity, solid content, dry shear strength, wet shear strength, FTIR Spectroscopy, SEM analysis, and shelf life were done to measure the adhesion properties of the bioadhesive. The result shows that the best shear strength, both dry and wet was obtained by adding 1.5% w/w kaolin powder with shear strength resulted 2,2684 MPa and with addition 2% w/w borax increased the shear strength up to 2,3207 MPa. Borax addition had been proven in improving the water resistance of the adhesive also inhibit fungal growth resulting extended the shelf life of the adhesive.